EFFECT OF IMMERSION IN COLD WATER AFTER TRAINING ON SUBJECTIVE PAIN IN THE MUSCLES IN THE ASPECT OF THEORETICAL ANALYSIS - Kabachkova, A.V.; Xiao, F.; Jiao, L.; Kapitanov, S.N. (Theory and Practice of Physical Culture, 2022)
Objective of the study was to conduct a meta-analysis of English-language literature sources on the issue of the effect of immersion in cold water after exercise on subjective muscle pain. Methods and structure of the study. A search was made for English-language scientific papers by keywords in various electronic databases (Pubmed, PEDro, Elsevier) for the period 2002-2022. Among the selected articles, those that addressed delayed muscle soreness syndrome and the effects of cold water immersion (CWI) immediately and/or 24 hours and/or 48 hours after high-intensity exercise were highlighted. Results and conclusions. It has been shown that the duration of such immersion influences the severity of pain sensations. At the same time, the temperature of the water had no effect on the severity of these sensations. It is best to use cold water immersion immediately after exercise. The article also presents the likely limitations of the study designs used, which must be taken into account when designing your own studies using cold water immersion.